2022
DOI: 10.1101/2022.05.25.493417
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Plasticity of mitochondrial function safeguards phosphorylating respiration during in vitro simulation of rest-phase hypothermia

Abstract: Many small animals routinely regulate resting body temperature several degrees below active-phase levels (rest-phase hypothermia), which reduces heat transfer rate and tissue oxygen demand and so may confer energy savings. Small birds that winter at high latitude show limited capacity for rest-phase hypothermia, meaning they cannot avoid upregulating heat production when facing winter cold. Substrates for upholding body temperature are provided by mitochondria in the form of adenosine triphosphate (ATP), but m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 91 publications
0
5
0
Order By: Relevance
“…This is achieved by maintaining a specific ratio between contraction kinetics and cycle duration, regardless of if the muscle is activated through a single stimulus or through a burst of stimuli (Askew and Marsh, 2001;Gladman and Askew, 2022;Marsh, 1990). Girgenrath and Marsh (1999) emphasised the close link between muscle operating frequency and twitch duration across a range of taxa and demonstrated…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is achieved by maintaining a specific ratio between contraction kinetics and cycle duration, regardless of if the muscle is activated through a single stimulus or through a burst of stimuli (Askew and Marsh, 2001;Gladman and Askew, 2022;Marsh, 1990). Girgenrath and Marsh (1999) emphasised the close link between muscle operating frequency and twitch duration across a range of taxa and demonstrated…”
Section: Discussionmentioning
confidence: 99%
“…The flight muscle of many insects performs best at temperatures ≥35°C (Wilmsen and Dzialowski, 2023), high frequency muscles of birds and bats are likely optimised to operate at similar body temperatures, when operating outside of these temperatures we see greatly reduced force output, such as with the pectoralis muscle of hummingbirds, where drastic temperature reductions of ≤20°C produce substantially reduced force (Reiser et al, 2013). Even in endotherms, such significant reductions of body temperature are commonly seen and behaviourally relevant: Small passerines reduce body temperature 5-10°C during the winter (Brodin et al, 2017;García-Díaz et al, 2023;Ruf and Geiser, 2015) and hummingbirds and bats reduce body temperature ≤20°C during daily torpor to reduce energetic costs (Luo et al, 2021;Shankar et al, 2022). The underlying muscle mechanics may now affect behavioural performance.…”
Section: Journal Of Experimental Biology • Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 Studies on birds have found that this makes it possible to assess mitochondrial function even from small (25-50 μl) blood samples [14][15][16] that can be safely collected in organisms <5 g. 17 This is not possible when measurements are performed using other mitochondria-rich blood cells, as is necessary in mammals. 18,19 Several recent bird studies indicate that blood cell respiration varies predictably in line with organismal-level energy demand over long 16,20 and short 21 time frames, and in the contexts of seasonal adaptation 22 and metabolic senescence. 23 Moreover, blood cell mitochondrial function seems amenable to epigenetic programming during embryonic development, 24,25 much like what is a well-known fact within human medicine.…”
Section: Introductionmentioning
confidence: 99%
“…2019; Casagrande et al . 2020) and short (García-Díaz et al 2022) time frames, and in the contexts of seasonal adaptation (Nord et al . 2021) and metabolic senescence (Dawson & Salmón 2020).…”
Section: Introductionmentioning
confidence: 99%